Казанские жиганы: роман / Евгений Сухов - Сухов Евгений Евгеньевич (Воровская Zона, 2012)
Экземпляры: Ф. 12 (20210503) / Инвентарный номер: 48351 / Цена: 45.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: С 91 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44